Increasing Students' Learning Motivation Through Problem Based Learning at SD Negeri 0405 Hutaraja Lamo - Lubis, Zainul Arifin; Hasibuan, Robinasari; Daulay, Hamnasari (Indonesian Journal of Education and Social Humanities, 2024)
This research aims to improve student learning outcomes in Islamic religious education learning using problem-based learning. This research is a classroom action research that uses four steps, namely planning, action, observation and reflection. The subject of this research is elementary school students. The data of this study was obtained by test and observation techniques. Tests are used to measure learning outcomes and observations are used to analyze the learning activities of teachers and students. The data analysis technique used in this study is descriptive statistics by comparing the results obtained with research success indicators. The results of the study show that problem-based learning can improve student learning outcomes in Islamic religious education learning. This can be seen from the increase in the percentage of student learning completeness in each cycle with details of the pre-cycle of 40.19%, the first cycle of 67.37% and in the second cycle it increased to 87.82%. Thus, the use of problem-based learning can be used as an alternative to improve student learning outcomes in Islamic religious education learning.